MECHANISMS OF PSYCHOSOCIAL MALADJUSTMENT IN PATIENTS WITH METABOLIC SYNDROME - Животовська Л. В.; Шкідченко О. І. (World of Medicine and Biology, 2015)
The attention is focused on complex and multidimensional study of the emotional disorder structure, which will allow to develop effective psychotherapeutic programs and will improve the prognosis of patients with metabolic syndrome. Complex and multidimensional clinical, experimental and psychological study of the emotional disorders structure and mechanisms of adaptation to the disease in patients with metabolic syndrome will specify the pathogenesis of their formation and determine the psycho-diagnostic "targets" for further psychotherapy. This in turn may have both theoretical and practical importance in the study of formation mechanisms and, consequently, the choice of "targets" for the development of psychocorrectionand psychotherapy programs.